Meaningful vectors of Uzbek story at the turn of XX-XXI centuries - Ergashevna, Kamilova Saodat; A.M., Boltabaeva; H, Alimova N.; M., Egamberdieva H. (International Journal of Psychosocial Rehabilitation, 2020)
As we know, the genre of storytelling enters the literary arena due to its mobility and promptness in transitional periods when there is a "revaluation of values", when the worldview changes, and the new reality and the system of views on the individual is only tested and found. These properties allow the story to focus on current, contemporary issues. It follows from the above that the story is one of the first to react to the change of the epoch, to the "new round" of social development, becomes a "landmark" genre of time, a kind of starting point in the change of character of social life. The peculiarity of the story is that it is actualized and manifests itself at a time when the main contradiction, which determines the essence of man and his time, just emerging and is in its infancy, hovers in the air and the main purpose of the story - to capture, demonstrate this contradiction. This article reveals the originality of the status relationship between the author, narrator and protagonist in the Uzbek story of the turn of the XX-XXI centuries through the prism of the problem and thematic fields of flash fiction of Uzbekistan. Three substantial vectors of the Uzbek story of the period under study are distinguished. The analysis of stories from these angles allows not only to show originality of development of a genre of the Uzbek story, but also to reveal a spectrum of the problems fixed by the story the end of XX - the beginning of XXI centuries reflecting a true picture of a human existence of the given period.